2007
DOI: 10.1111/j.1365-3040.2007.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression differences for genes involved in lignin, glutathione and sulphate metabolism in response to cadmium in Arabidopsis thaliana and the related Zn/Cd‐hyperaccumulator Thlaspi caerulescens

Abstract: Cadmium (Cd) is a widespread, naturally occurring element present in soil, rock, water, plants and animals. Cd is a non-essential element for plants and is toxic at higher concentrations. Transcript profiles of roots of Arabidopsis thaliana (Arabidopsis) and Thlaspi caerulescens plants exposed to Cd and zinc (Zn) are examined, with the main aim to determine the differences in gene expression between the Cd-tolerant Zn-hyperaccumulator T. caerulescens and the Cd-sensitive non-accumulator Arabidopsis. This compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(192 citation statements)
references
References 82 publications
5
177
0
10
Order By: Relevance
“…Analysis of the Arabidopsis transcriptome using the Arabidopsis microarray database and analysis toolbox GENEVESTIGATOR (Zimmermann et al, 2004) confirmed that MYB72 is not activated in response to any of the hormones or biological agents tested (data not shown), suggesting that the induction of MYB72 in the roots upon colonization by nonpathogenic rhizobacteria is highly specific. However, low iron conditions or treatment of Arabidopsis roots with an excess amount of zinc do induce the expression of MYB72 in the roots (Colangelo and Guerinot, 2004;Van de Mortel et al, 2008). Studies by Thomine et al (2003) and Van A, RNA gel-blot analysis of MYB72 transcript levels in roots and shoots of 5-week-old wildtype Col-0 plants and the mutant and transgenic lines EV (EV control), myb72-1, and 35S:MYB72-OX1 to -OX7.…”
Section: Specificity Of Myb72 Gene Expressionmentioning
confidence: 99%
“…Analysis of the Arabidopsis transcriptome using the Arabidopsis microarray database and analysis toolbox GENEVESTIGATOR (Zimmermann et al, 2004) confirmed that MYB72 is not activated in response to any of the hormones or biological agents tested (data not shown), suggesting that the induction of MYB72 in the roots upon colonization by nonpathogenic rhizobacteria is highly specific. However, low iron conditions or treatment of Arabidopsis roots with an excess amount of zinc do induce the expression of MYB72 in the roots (Colangelo and Guerinot, 2004;Van de Mortel et al, 2008). Studies by Thomine et al (2003) and Van A, RNA gel-blot analysis of MYB72 transcript levels in roots and shoots of 5-week-old wildtype Col-0 plants and the mutant and transgenic lines EV (EV control), myb72-1, and 35S:MYB72-OX1 to -OX7.…”
Section: Specificity Of Myb72 Gene Expressionmentioning
confidence: 99%
“…Response processes are specific for each different stress conditions as shown by the lack of any uniform transcriptome profile of plants subjected to different types of stress such as heat or cold, drought or salinity, strong light, mechanical and heavy metal stress (Cheong et al, 2002;Debnath et al, 2011;Kreps et al, 2002;Mantri et al, 2012;Marco et al, 2011;Rizhsky et al, 2004;Shen et al, 2012;Van de Mortel et al, 2008;Yang and Chu, 2011). Integrated responses to different biotic and abiotic stress conditions are regulated by the hormonal network of the plants, including auxins, cytokinins, abscisic acid (ABA), 3-indole acetic acid (IAA) and brassinosteroids (Bajguz and Hayat, 2009), which combined with many metabolites (i.e., jasmonic acid and ethylene) and secondary messengers (i.e., Ca 2+ ) play a pleiotropic regulatory key role.…”
Section: Introductionmentioning
confidence: 99%
“…The Al-sensitive IAC-Uruguai plants showed an increase in the number of root cells with highly lignified cell walls. In some cases, lignification may be beneficial, forming a physical barrier against toxic metals (Van de Mortel et al 2008). Alternatively, in a number of plant species, increased lignification occurs in response to mechanical damage in tissues, such as rupture of epidermal cell layer (Moura et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Absolute integrity percentage, estimated based on electrolyte leakage (Vásquez-Tello et al 1990), and relative water content were measured in the youngest fully expanded leaf at 1, 5, 10 and 15 days after the AlCl 3 application. Leaf discs were placed in closed tubes containing 10 mL of deionized water and incubated in the dark for 24 h, at 8 ºC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation